Study on Model and Tests of Sheet Pile Wall with a Relieving Platform - Ming Zhang; Wei Wang; Ronghua Hu; Ziyi Wang (Advances in Civil Engineering)
A new type of retaining wall, the sheet pile wall with a relieving platform, is introduced in this paper. Based on the prototype retaining wall with a height of 12 meters, the model tests with a geometric similarity ratio of 7 are designed and we focus on the model production and analysis on the test results. Some comparative analyses between the measured values and the calculation values by using the theoretical calculation method and finite difference method are carried out, including Earth pressure behind the wall, prepile resistance force, the bending moment, and the deformation of rib pillars in the retaining wall. The results show that Earth pressure behind the wall has a linear increase with the depth and lies between Rankine Earth pressure and Earth pressure at rest. Moreover, the prepile resistance force can be approximated by the m method, and the bending moment can be also used for approximate calculation by the m method and is larger than the results calculated by the finite difference method. It is also observed that there is a zero-displacement point on the pile bottom, and the Earth pressure above the point behind the pile develops from Earth pressure at rest to the active Earth pressure; the Earth pressure under the point behind the pile develops from Earth pressure at rest to the passive Earth pressure. Therefore, the Earth pressure behind the bottom wall is larger than the calculated value by the Rankine theory. Finally, the displacement of the rib pillars is greater than the calculated results using the finite difference method and exceeds the standard requirements, owing to the failure of the retaining wall, and the unloading board needs to be constructed to improve the retaining wall’s behaviour. These findings verify the model’s credibility and provide an underpinning for studying the behavior of the retaining wall.